CAFRAD related activities to food security and food safety: training workshops on the preparation and evaluation of agricultural projects - Michael L. (Mainstreaming gender dimensions in water management for food security and food safety, 2007)
The objective of this paper is to give some information on two high-level training programmes for Anglophone African countries, organized by the African Training and Research Centre in Administration for Development (CAFRAD). The first programme was a training workshop on the preparation and evaluation of agricultural projects and the second one was a training course on capacity-building in agricultural and rural development project preparation and monitoring. A workshop on managing water resources for sustainable development in Africa was envisaged to be carried out in 2005, with emphasis on local communities' participation.
2. Regional Coordination Workshop of GEWAMED (Mainstreaming Gender Dimensions into Water Resources Development and Management in the Mediterranean Region), 2007/03/12-14, Larnaca (Cyprus)